Post-COVID Library: Educating Children to Media and Information Literacy through UNESCO’s Memory of the World Programme - Zhang, Ruohan; Moreau, Linh Anh (Access: An International Journal of Nepal Library Association, 2022)
The COVID-19 pandemic has severely disrupted children's education in schools, and reflects the urgent demands of children and their educators for diverse learning channels and materials. Memory institutions such as libraries, archives and museums, as repositories of reliable sources of information and knowledge service provider, have a responsibility to contribute to the cultural and media literacy education of children. Therefore, memory institutions should explore innovative ways to safeguard and utilize documentary collections in media and information literacy education for people and especially children, and share and promote good practices. These efforts will also inspire younger generations to participate in the preservation and transmission of historical records.